2010
DOI: 10.5194/acp-10-7457-2010
|View full text |Cite
|
Sign up to set email alerts
|

NO<sub>2</sub> photolysis frequencies in street canyons

Abstract: Abstract. Photolysis frequencies for NO 2 are modeled for the conditions in urban streets, which are taken into account as canyons with variable height and width. The effect of a street canyon is presented with absolute values and as a ratio RJ of the photolysis frequency within the street compared to that with free horizon. This allows further use of the existing photolysis parameterizations. Values are presented for variable solar elevation and azimuth angles, varying atmospheric conditions and different str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The value for the photolysis frequency is a rough estimate for clear viewing conditions [cf. Koepke et al , 2010], the actual one might be lower, which would lead to an even lower L Leighton .…”
Section: Results Discussion and Comparison With Other Datamentioning
confidence: 99%
“…The value for the photolysis frequency is a rough estimate for clear viewing conditions [cf. Koepke et al , 2010], the actual one might be lower, which would lead to an even lower L Leighton .…”
Section: Results Discussion and Comparison With Other Datamentioning
confidence: 99%
“…Eco Physics AG PLC 760), and the averaged measured spectral output of six individual BLC UV-LED arrays of varying running hours. Also shown is the NO 2 quantum yield (Gardner et al, 1987;Koepke et al, 2010). It can be discerned that the UV-LED output overlaps fully with the NO 2 absorption band and the NO 2 quantum yield and is therefore photon-efficient.…”
Section: Possible Photolytic Interferences Of Blcsmentioning
confidence: 99%
“…In contrast, it has been reported that the photolysis of NO 2 can be considerably decreased (by 40 % compared to open areas) within street canyons (Koepke et al, 2010) because incoming direct and diffuse sun light at large zenith angles may be obstructed by the buildings. Koepke et al (2010) suggest the application of a scaling factor of 0.5 to adjust J NO 2 from a free horizon to street canyons. it is expected that the photochemical steady state assumption was fulfilled.…”
mentioning
confidence: 81%